2006
DOI: 10.1021/ma060750e
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of PPE in Lamellar Self-Assembled PS-b-P4VP(PDP) Supramolecules and PS-b-P4VP Diblock Copolymers

Abstract: Self-assembled blends of PS-b-P4VP(PDP) supramolecules, obtained by hydrogen bonding of pentadecylphenol (PDP) side chains to poly(4-vinylpyridine), and poly(2,6-dimethyl-1,4-diphenyl oxide) (PPE) were investigated by thermal analysis and small-angle X-ray scattering (SAXS) and compared with blends of PS-b-P4VP and PPE. Differential scanning calorimetry (DSC) measurements showed a single composition dependent T g of the PPE/PS layers for both systems, demonstrating that PPE is distributed throughout the PS lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
44
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 51 publications
(132 reference statements)
1
44
1
1
Order By: Relevance
“…[1][2][3][4] It has been demonstrated that poly(4-vinyl pyridine) (P4VP) is able to interact strongly with polymers of a wide variety of structures through hydrogen bonding, such as poly(vinyl phenol) (PVPh), [5][6][7][8] poly(vinyl alcohol), [9] and phenolic resin. [10] It is well known that the nature of the solvent medium can control complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] It has been demonstrated that poly(4-vinyl pyridine) (P4VP) is able to interact strongly with polymers of a wide variety of structures through hydrogen bonding, such as poly(vinyl phenol) (PVPh), [5][6][7][8] poly(vinyl alcohol), [9] and phenolic resin. [10] It is well known that the nature of the solvent medium can control complex formation.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32] In particular, hydrogen-bonded polymer-surfactant complexes of polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) and alkyl phenols, such as pentadecyl phenol (PDP) and dodecyl phenol (DDP), lead to discrete PS-b-P4VP nanorods with a PS core and P4VP corona. [27,33,34] The advantages of such a supramolecular approach include: i) reduction of the glass-transition temperature (T g ) of both phases (T g (PS) ≈ 67°C; T g (P4VP/PDP) ≈ room temperature) [35] to allow shear alignment at moderate temperatures for improvement of the self-assembled structures; and ii) preparation of PS-core-P4VP-corona nano-objects by simple dissolution of PDP. Electroless deposition using Pd and adsorption of CdSe nanoparticles allows granular inorganic coatings on the PS-b-P4VP rods.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Initially, most of the studies involved the blends of a block copolymer with a homopolymer identical to one of the blocks, i.e. A-b-B/A or A-b-B/B.…”
Section: Introductionmentioning
confidence: 99%